Effect of Watermelon Rind Powder on Quality Attributes and Storage Stability of Raw Pork and Pork Meat balls - Mahapatra, G.; Biswas, S.; Patra, G.; Vidyarthi, A . K.; Banerjee , R. (Journal of Meat Science, 2019)
This study was conducted to analyze the anti-oxidant and anti-microbial effect of wa-termelon rind powder on raw minced pork as well as on pork meatballs stored at refrigerated (4+1°C) temperature for a period of 21 days. Watermelon rind powder was incorporated to raw minced pork as well as pork meatball mixture at the rate of 1.0%, 1.5% and 2.0% on w/w basis. Based upon the Thiobarbituric Acid Reacting Substances (TBRAS) values, Total Plate Count (TPC), Total Psychrotrophic Count (TPSC), Total Coliform Count (TCC) and Yeast and Mould Count (YMC) it was concluded, watermelon rind powder was capable of enhancing the storage stability of the product. Incorporation of watermelon rind powder in pork meatball mixture en-hanced the desirable physico-chemical and textural properties, although sensory evaluation re-vealed poorer acceptability compared to control samples.